Novel tools to quantify total, phospho-Ser129 and aggregated alpha-synuclein in the mouse brain - Benjamin Guy Trist; Courtney Jade Wright; Alejandra Rangel; Louise Cottle; Asheeta Prasad; Nanna Møller Jensen; Hjalte Gram; Nicolas Dzamko; Poul Henning Jensen; Deniz Kirik (npj Parkinson's Disease)
Abstract Assays for quantifying aggregated and phosphorylated (S129) human α-synuclein protein are widely used to evaluate pathological burden in patients suffering from synucleinopathy disorders. Many of these assays, however, do not cross-react with mouse α-synuclein or exhibit poor sensitivity for this target, which is problematic considering the preponderance of mouse models at the forefront of pre-clinical α-synuclein research. In this project, we addressed this unmet need by reformulating two existing AlphaLISA® SureFire® Ultra™ total and pS129 α-synuclein assay kits to yield robust and ultrasensitive (LLoQ ≤ 0.5 pg/mL) quantification of mouse and human wild-type and pS129 α-synuclein protein. We then employed these assays, together with the BioLegend α-synuclein aggregate ELISA, to assess α-synuclein S129 phosphorylation and aggregation in different mouse brain tissue preparations. Overall, we highlight the compatibility of these new immunoassays with rodent models and demonstrate their potential to advance knowledge surrounding α-synuclein phosphorylation and aggregation in synucleinopathies.